2001
DOI: 10.1023/a:1014009328207
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The response of splenic CD4 T cells from ovalbumin (OVA)-specific T cell receptor (TCR) transgenic mice after long-term feeding of a diet containing this antigen was examined. These CD4 T cells exhibited a decreased response to OVA peptide stimulation, in terms of proliferation, interleukin-2 secretion, and CD40 ligand expression, compared to those from mice fed a control diet lacking OVA, demonstrating that oral tolerance of T cells had been induced through oral intake of the antigen. We investigated the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In contrast, under conventional breeding conditions, OVA23-3 mice have been reported to serve as an experimental model for oral tolerance and food allergy. Indeed, oral tolerance can be induced in spleen (SP) T cells from these mice when fed an OVA-containing diet over a long period [16,17]. It has also been reported that OVA23-3 mice produce OVA-specific antibodies in the serum and develop intestinal inflammation in a Th2-dependent manner after intake of an OVA-containing diet [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, under conventional breeding conditions, OVA23-3 mice have been reported to serve as an experimental model for oral tolerance and food allergy. Indeed, oral tolerance can be induced in spleen (SP) T cells from these mice when fed an OVA-containing diet over a long period [16,17]. It has also been reported that OVA23-3 mice produce OVA-specific antibodies in the serum and develop intestinal inflammation in a Th2-dependent manner after intake of an OVA-containing diet [18,19].…”
Section: Introductionmentioning
confidence: 99%